TEACHERS’ AND LEARNERS PERCEPTIONS OF LANGUAGE TEACHING STRATEGIES IN MULTI CHANNEL LEARNING SYSTEM - Karjo, Clara Herlina (Universitas Pendidikan Indonesia, 2011)
Abstract: In learning a foreign language, learners usually apply certain learning strategies. Similarly, in teaching a foreign language, especially English, teachers also need teaching strategies. Issues related to learners’ learning strategies have been discussed over the years; however, issues related to teachers’ teaching strategies have not been researched thoroughly. Effective teaching strategies are particularly important for teachers who are teaching big classes in multi channel learning system as applied in Bina Nusantara University. This study had two aims: first, to investigate the teachingstrategies employed by Binus English teachers and second, to find out the intersection between teachers and students regarding the teaching strategies employed in the classroom. Using questionnaires for teachers and students, this study examined the frequency of strategy used by students and teachers. The results showed that teachers and students had different perceptions on the strategies/activities that occurred in the classroom. The implications of these results for the teaching/learning situation are discussed.Keywords: multi channel learning, teaching strategies, perception, teachers, students